Pervasive Gene Conversion in Chromosomal Inversion Heterozygotes - Korunes, Katharine L. (Mol Ecol, 2018)
Chromosomal inversions shape recombination landscapes, and species differing by inversions may exhibit reduced gene flow in these regions of the genome. Though single-crossovers within inversions are not usually recovered from inversion heterozygotes, the recombination-barrier imposed by inversions is nuanced by non-crossover gene conversion. Here, we provide a genome-wide empirical analysis of gene conversion rates both within species and in species hybrids. We estimate that gene conversion occurs at a rate of 1 × 10(−5) to 2.5 × 10(−5) converted sites per bp per generation in experimental crosses within Drosophila pseudoobscura and between D. pseudoobscura and its naturally-hybridizing sister species D. persimilis. This analysis is the first direct empirical assessment of gene conversion rates within inversions of a species hybrid. Our data show that gene conversion rates in interspecies hybrids are at least as high as within-species estimates of gene conversion rates, and gene conversion occurs regularly within and around inverted regions of species hybrids, even near inversion breakpoints. We also found that several gene conversion events appeared to be mitotic rather than meiotic in origin. Finally, we observed that gene conversion rates are higher in regions of lower local sequence divergence, yet our observed gene conversion rates in more divergent inverted regions were at least as high as in less divergent collinear regions. Given our observed high rates of gene conversion despite the sequence differentiation between species, especially in inverted regions, gene conversion has the potential to reduce the efficacy of inversions as barriers to recombination over evolutionary time.